DIFFICULTIES OF BARANGAY COUNCIL IN CRAFTING LOCAL LEGISLATION IN PLARIDEL, ABORLAN, PALAWAN - Maribel D. Limsa; Jonel R. Crisosto (Scholar Express Journal, 2023)
This study generally aimed to determine the difficulties of barangay council officials in crafting local legislation in Plaridel, Aborlan, Palawan which was conducted from December 19-21, 2022 at Plaridel, Aborlan, Palawan. A descriptive method employing survey questionnaire was used to gather data from the respondents. Results showed that barangay councils faced minor difficulties in crafting local legislation as their competence fall short very slightly. Moreover, they experienced slight difficulty in following the processes in the crafting of local legislations. However, barangay council officials perceived that they were not facing difficulty in the performance of their duties and responsibilities as local legislators.
Keywords: Barangay; Local Legislation; Sangguinang Barangay